Effectiveness and Nephrotoxicity of Intravenous Polymyxin B in Carbapenem-Resistant Gram-Negative Bacterial Infections Among Chinese Children - Jia, Xuedong; Yin, Zhao; Zhang, Wan; Guo, Conghui; Du, Shuzhang; Zhang, Xiaojian (Frontiers in Pharmacology, 2022)
.Background: No clinical study on the use of polymyxin B in Chinese children has been reported, thus making it difficult for pediatric clinicians to rationally select these drugs. Methods: A retrospective analysis of children treated with polymyxin B during hospitalization in a hospital from June 2019 to June 2021 was conducted to analyze its effectiveness and the incidence of acute kidney injury (AKI) during treatment with polymyxin B. Results: A total of 55 children were included in this study, and the results showed that the intravenous polymyxin B-based regimen had an effective rate of 52.7% in the treatment of Carbapenem-resistant Gram-negative bacterial (CR-GNB) infection in children. The results of the subgroup analysis showed that the course of treatment was longer in the favorable clinical response group than in the unfavorable outcome group (P=0.027) and that electrolyte disturbances in children during the course of treatment could lead to unfavorable clinical outcomes (P=0.042). The risk of incidence of AKI during treatment was 27.3%, and the all-cause mortality rate in the children on their discharge from the hospital was 7.3%. Conclusions: Polymyxin B can be used as a treatment option for CR-GNB infection in children, but it increases the risk of AKI. Therefore, the monitoring of kidney function should be strengthened.